2006
DOI: 10.1089/jpm.2006.9.631
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Evaluation of Bupropion for the Treatment of Hot Flashes

Abstract: Bupropion is commonly used in the treatment of nicotine dependence and depression, and in most people, does not cause sexual dysfunction, weight gain, or sedation. Given its attractive side effect profile, the efficacy of other newer antidepressants against hot flashes and anecdotal observations of resolution of hot flashes in some patients taking bupropion for nicotine dependence, it was decided to explore its clinical activity as a hot flash remedy in a pilot study. Between January 1999 and October 2004, 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 47 publications
1
11
0
2
Order By: Relevance
“…[63] A final trial of mirtazapine reporting insomnia outcomes in the treatment of hot flushes was identified but, as approximately 40% of the study participants were post-menopausal women with no history of breast cancer, the trial was excluded. [64] …”
Section: Resultsmentioning
confidence: 99%
“…[63] A final trial of mirtazapine reporting insomnia outcomes in the treatment of hot flushes was identified but, as approximately 40% of the study participants were post-menopausal women with no history of breast cancer, the trial was excluded. [64] …”
Section: Resultsmentioning
confidence: 99%
“…13 Also, bupropion, an antidepressant, is no different from placebo in reducing hot flashes. 14 Furthermore, Nelson et al 13 recommend these nonhormonal agents for highly symptomatic women who cannot take estrogen and highlight the need for larger, more rigorous trials using standardized outcomes.…”
mentioning
confidence: 99%
“…120 A non-randomized study of mirtazapine 15 to 30 mg per day showed a 59% reduction in hot flashes in 22 women with a risk or history of breast cancer. 121 Recently, an open-label trial was conducted to assess the efficacy of mirtazapine for reliving vasomotor symptoms in 40 breast cancer patients. 122 Results showed a 56% reduction of hot flash frequency and 62% reduction in hot flash scores as compared to baseline; however only 20 participants (50%) completed the 12-week study.…”
Section: Therapeutic Optionsmentioning
confidence: 99%